THE ROLE OF CYP17A1 IN ADENOCARCINOMA OF THE PROSTATE AT SARDJITO GENERAL HOSPITAL - Prayogo, Dwi; Soeroharjo, Indrawarman (Indonesian Urological Association, 2020)
Objective: The purpose of this study is to determine the relationship and role of CYP17A1 gene expression to androgen biosynthesis activity in prostate cancer patients. Material & Methods: The samples of this study are patients diagnosed with prostate adenocarcinoma based on histopathology examination who underwent TURP surgery at Sardjito General Hospital. A total of 30 samples were examined for PCR to determine the presence and absence of CYP17A1 gene expression. CYP17A1 gene expression was analyzed with the patient’s age, stage, organ metastasis, Gleason score, and PSA value. Results: Analysed using Chi-Square Tests, p=0.784 was obtained on expression of CYP17A1 gene with patient’s age, p=0.469 on expression of CYP17A1 gene with staging tumor, p=0.855 on expression of CYP17A1 gene with presence or absence of organ metastasis, p=0.059 on expression of CYP17A1 gene expression with total Gleason score, p=0.895 on expression of CYP17A1 gene with PSA value. Conclusion: There was no association between CYP17A1 gene expression and intratumoral androgen biosynthesis activity based on the patient’s age, patient’s clinical stage, organ metastasis, Gleason score, and PSA value.